Prediction of S&P500 stock market movement using Twitter sentiment analysis - Horo, Omar Hannan (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: Twitter is amongst the biggest social networking services, offering its services to over 350 million active users as of 2021. For over the past few years, Twitter has been the most used social network platform as a tool of interaction between investors and stock market given its convenience and ability to move information from one part to another in a very short time. For over years, econometrics had always turn to the basic Ordinary Least Regression (OLS) to analyze the relationship between two variables and how much impact one variable could have another. However, during OLS analysis, the assumption is that the squared values of all errors terms at any particular point is constant (Homoskedasticity). Therefore, for a given set of data in a time series with different error terms (Heteroskedasticity) may result to a slight sense of false analysis and forecasting precision, hence leading us to go with ARCH and GARCH models, where heteroskedasticity is basically considered as variance to be accounted for and modeled. The aim of this study was to determine whether there is a significance impact of sentiment to the stock return in the time series. Despite several related studies, most papers mostly used Ordinary Least Squares with an assumption of linearity. Despite the original OLS showing significant influence of sentiments in our model, ARCH and GARCH models concluded that sentiment was not a significant predictor in the conditional variance.

ÖZET: Twitter, 2021 yılı itibarıyla 350 milyonu aşkın aktif kullanıcıya hizmet sunan en büyük sosyal ağ servisleri arasında yer almaktadır. Twitter, geçtiğimiz yıllarda yatırımcılar ve borsa arasında bir etkileşim aracı olarak en çok kullanılan sosyal ağ platformu olmuştur. Bilgileri çok kısa sürede bir parçadan diğerine taşıma kolaylığı ve yeteneği olan bir platformudur. Yıllar boyunca, ekonometri, iki değişken arasındaki ilişkiyi ve bir değişkenin diğerini ne kadar etkileyebileceğini analiz etmek için her zaman temel Sıradan En Az Regresyona (OLS) yöneldi. Bununla birlikte, OLS analizi sırasında, herhangi bir noktadaki tüm hata terimlerinin kare değerlerinin sabit olduğu varsayımıdır (Homoskedastisite). Bu nedenle, farklı hata terimlerine (Heteroskedastisite) sahip bir zaman serisindeki belirli bir veri seti için, hafif bir yanlış analiz ve tahmin kesinliği hissi ile sonuçlanabilir, bu nedenle bizi değişen varyanslılığın temelde varyans olarak kabul edildiği ARCH ve GARCH modellerine yönelmemize neden olabilir, hesaplanacak ve modellenecektir. Bu çalışmanın amacı, zaman serilerinde duyarlılığın hisse senedi getirisi üzerinde anlamlı bir etkisinin olup olmadığını belirlemektir. Birkaç ilgili çalışmaya rağmen, çoğu makale çoğunlukla doğrusallık varsayımıyla Sıradan En Küçük Kareleri kullandı. Modelimizde duyguların önemli etkisini gösteren orijinal OLS'ye rağmen, ARCH ve GARCH modelleri, duyarlılığın koşullu varyansta önemli bir tahmin edici olmadığı sonucuna varmıştır.
Twitter duyarlılık analizi kullanarak S&P500 hisse senetleri hareketi tahmini
Keywords: ARCH modeli; Duygu Analizi; GARCH modeli; Ekonometri; Oynaklık; ARCH Model; Sentiment Analysis; GARCH MODEL; Econometrics; Volatility